MEMBANGUN DAYA SAING TENAGA KERJA INDONESIA MELALUI PENINGKATAN PRODUKTIVITAS - Latif Adam (Jurnal Kependudukan Indonesia, 2016)
This paper analyzes current status of the Indonesian labor competitiveness in its ASEAN labor competitiveness context. Labor competitiveness is a key factor that could facilitate and accelerate an economy’s competitiveness. This plays an important role as the main engine of economic growth. Data used is secondary data from the Asian Productivity Organization (APO), ILO, UNDP, and Badan Pusat Statistik, Indonesia. By using descriptive analysis and harnessing labor productivity as a proxy for labor competitiveness, it was found that the position and acceleration of the Indonesian labor competitiveness lag behind those in its several ASEAN neighbors. Main policy challenge that need to be addresed is to reform human resource development strategy with a long-term gradually and simultaneously with efforts to find solutions to the problems of labor competitiveness in the short-medium term. In addition to improving the educational system and resolve skills improvement programs, the government needs to strengthen the integration of its national economy into the global economy as the driving force of skilled labor mobility and channel for knowledge and skills transfers.